DIFFERENT RAW MATERIAL EFFECT IN PREFERENCE LEVEL AND MOISTURE CONTENT OF SEASONING POWDER - Mutamimah, Dewi; Mahesvarah, Titah; Envendi, Jefri (Chanos Chanos, 2023)
Seasoning is widely used in many dishes for the example fried rice, meatball, chicken soup, beef stew for enhancing the flavor of food. The food will have a good taste by adding some seasoning. It will give umami taste and make people even more enjoying their meal. The purposes of this research were to know the preference level and moisture content of seasoning powder with different raw material. The analysis used in research were moisture content by gravimetric method and preference level consist of appearance, taste, aroma, texture by hedonic test. The moisture content of the anchovy, seaweed and white oyster mushroom seasoning were 10%, 20% and 15% respectively. The appearance levels were 3.7, 2.5, and 4.3. the taste level were 3.5, 1.8, and 4.5. The aroma levels were 1.9, 2.6 and 3.8. The texture levels were 2.6, 1.7 and 4.2.